f ( 9 9 9 1 ) + f ( 9 9 9 2 ) + f ( 9 9 9 3 ) + ⋯ + f ( 9 9 9 9 9 8 )
If f ( x ) = 1 − f ( 1 − x ) for all real x , evaluate the expression above.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
a(n) = a + d(n-1)
9 9 9 9 9 8 = 9 9 9 1 + 9 9 9 1 (n-1), n = 998, which can easily be seen has 998 terms as the function is the complement of the complement or itself. ex. f( 9 9 9 1 ) = 9 9 9 1
S = 2 9 9 8 (2( 9 9 9 1 )+(998-1) 9 9 9 1 )
S = 499
Problem Loading...
Note Loading...
Set Loading...
f ( x ) = 1 − f ( 1 − x ) → f ( x ) + f ( 1 − x ) = 1
The form of the function tells us that, Gaussian pairing tool might be useful here.
Let, S = f ( 9 9 9 1 ) + f ( 9 9 9 2 ) + f ( 9 9 9 3 ) + . . . + f ( 9 9 9 9 9 7 ) + f ( 9 9 9 9 9 8 ) → S = f ( 9 9 9 9 9 8 ) + f ( 9 9 9 9 9 7 ) + f ( 9 9 9 9 9 6 ) + . . . + f ( 9 9 9 2 ) + f ( 9 9 9 1 )
With addition, 2 S = ( f ( 9 9 9 1 ) + f ( 9 9 9 9 9 8 ) ) + ( f ( 9 9 9 2 ) + f ( 9 9 9 9 9 7 ) ) + . . . + ( f ( 9 9 9 9 9 8 ) + f ( 9 9 9 1 ) ) . = ∑ a = 1 9 9 8 ( f ( a ) + f ( 1 − a ) ) = ∑ a = 1 9 9 8 1 = 9 9 8
Thus we get, 2 S = 9 9 8 → S = 4 9 9 which is the desired answer.